2021
DOI: 10.3389/fnins.2021.680104
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Causal Relationship Between Human Blood Metabolites and Five Neurodegenerative Diseases With GWAS Summary Statistics

Abstract: Background: Neurodegenerative diseases (NDDs) are the leading cause of disability worldwide while their metabolic pathogenesis is unclear. Genome-wide association studies (GWASs) offer an unprecedented opportunity to untangle the relationship between metabolites and NDDs.Methods: By leveraging two-sample Mendelian randomization (MR) approaches and relying on GWASs summary statistics, we here explore the causal association between 486 metabolites and five NDDs including Alzheimer’s Disease (AD), amyotrophic lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 86 publications
(122 reference statements)
0
7
0
Order By: Relevance
“…Sun et al (2019) report increases associated with increased stroke risk, possibly due to increased blood pressure. Chen et al (2021) see a negative correlation with AD but a positive correlation with frontotemporal dementia (FTD). The relationship of hexadecanedioate with AD amelioration may be important, complex, and non-linear.…”
Section: Results and Intermediate Logical Steps (Lemmas)mentioning
confidence: 99%
See 3 more Smart Citations
“…Sun et al (2019) report increases associated with increased stroke risk, possibly due to increased blood pressure. Chen et al (2021) see a negative correlation with AD but a positive correlation with frontotemporal dementia (FTD). The relationship of hexadecanedioate with AD amelioration may be important, complex, and non-linear.…”
Section: Results and Intermediate Logical Steps (Lemmas)mentioning
confidence: 99%
“…For example, one might expect a gene implicated by AD GWAS to have its gene product identified, or an analyte functionally associated with that gene. None of the candidate COCOA mediators intersect with a list of GWAS-implicated genes (Seto et al, 2021) (Chen et al, 2021). They suggestively associated 164 metabolites with the risk of at least one neurodegenerative disease.…”
Section: G Lemma 7: Several Identified Mechanisms Have Considerable P...mentioning
confidence: 96%
See 2 more Smart Citations
“…N-acetylcysteine can regulate a variety of pathophysiological processes, including oxidative stress, apoptosis, mitochondrial dysfunction, and imbalance of glutamate and dopamine neurotransmitter systems ( 31 ). Other studies have shown that 2-methoxy acetaminophen sulfate has an intervention effect on neurodegenerative diseases (such as amyotrophic lateral sclerosis and frontotemporal dementia) ( 32 ). Phenylalanine is one of the essential aromatic amino acids of the human body and can only be obtained from the outside world by food, because there is no relevant synthesis pathway in the human body.…”
Section: Discussionmentioning
confidence: 99%